PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMAAN KEANGGOTAAN KARANG TARUNA DESA CUKIR - Achmad Zakariya, Edo; Heru Mujianto, Ahmad; Zein Vitadiar , Tanhella; Kristianto , Hery (Inovate, 2025)
This research aims to apply the Simple Additive Weighting (SAW) method as a decision support tool for determining the eligibility of new members in the village youth organization. The Simple Additive Weighting method is chosen for its ability to handle various criteria and rank candidates based on the weighted sum of each criterion. This process involves several stages, including identifying assessment criteria, assigning weights to each criterion, normalizing values, and final calculations to determine candidate rankings. The research findings show that the SAW method can be effectively and efficiently implemented, providing objective and transparent results in the new member selection process. In this study, the algorithm used is the Simple Additive Weighting algorithm. The results indicate that the selection system for Karang Taruna members functions well. With the testing of 20 applicant inputs, the system can calculate accurately. The system's assessment scored a total of 1217.5, and the manual calculation scored 1270.4, resulting in an accuracy percentage of 95.83%. Thus, it can be concluded that the system's accuracy is good and can facilitate obtaining value data from the selection of Karang Taruna member applicants. Keywords: Bumdesa, Simple Additive Weighting.